THE RELATIONSHIP BETWEEN TEACHER'S CREATIVITY IN TEACHING AND LEARNING ACHIEVEMENT OF V-GRADE STUDENTS OF SDN MEPANGA - Wayan Sudarsana (STAH Dharma Sentana Sulawesi Tengah, 2023)
This study aims to determine the relationship between teacher creativity in teaching and learning achievement of fifth grade students at SDN Mepanga. The type of research used is descriptive quantitative. Data collection techniques using interviews and questionnaires. The data obtained from the questionnaire is then processed into quantitative data by means of each answer choice being weighted using a Likert. The data analysis technique used is descriptive analysis technique and quantitative data. Based on the results of the descriptive analysis of the 15 students who were respondents who stated that the teacher's creativity was very good, there were 6 respondents (40%) while those who stated that the teacher's creativity was good were 9 respondents (60%). This shows that the teacher's creativity is already in a good category as evidenced by the information obtained from the results of filling out the questionnaire and for the report card scores of the 24 populations taken from a sample of 15 respondents, it shows an increase in the lowest average score starting from 64.4 to an average value highest 79.7. From the description above it can be said that there is a relationship between teacher creativity in teaching and student achievement.